2009
DOI: 10.1593/neo.09296
|View full text |Cite
|
Sign up to set email alerts
|

Defective Infiltration of Natural Killer Cells in MICA/B-Positive Renal Cell Carcinoma Involves β2-Integrin-Mediated Interaction

Abstract: We have explored MICA/B expression and its relationship with innate inflammatory infiltrate in renal cell carcinoma (RCC). The expression of MICA/B, CD16, CD56, and CD68 in 140 RCC lesions contained in a tissue microarray (TMA) was investigated by immunohistochemistry. MICA/B gene and protein expressions in Caki-1 cells were analyzed by reverse transcription-polymerase chain reaction and flow cytometry, respectively. Natural killer (NK) cells were studied by flow cytometry. All the RCC lesions (n = 140) were M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
55
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 36 publications
6
55
0
Order By: Relevance
“…These results provide potential mechanistic insights for a number of observations previously made by others and by ourselves (2)(3)(4)(5). Indeed, we found that NK cell infiltration is poor, if at all detectable, in various types of human cancers.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…These results provide potential mechanistic insights for a number of observations previously made by others and by ourselves (2)(3)(4)(5). Indeed, we found that NK cell infiltration is poor, if at all detectable, in various types of human cancers.…”
supporting
confidence: 78%
“…Further studies using autologous cancer cells are warranted to clarify whether molecular mechanisms underlying impaired NK cell functions in a tumor setting are specifically related to neoplastic transformation (3). Nevertheless, the data by Pietra and colleagues, Mamessier and colleagues, and Erdag and colleagues (1, 2, 4, 7), together with our observations question A B Figure 1.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Sarcomatoid changes can also occur in clear cell renal carcinoma and is associated with poor prognosis [5,9]. Most renal cell carcinomas have little inflammatory response, but sometimes an intense lymphocytic or neutrophilic infiltrate with natural killer cells is present [10] and there is an association between a strong lymphocytic infiltration and worse outcome [11]. Clear cell renal cell carcinomas most commonly metastasize hematogeneously via the vena cava primarily to the lung.…”
Section: The Who Classification Of Renal Cancermentioning
confidence: 99%
“…Renal cell carcinoma is the most common type of kidney cancer and follows an unpredictable disease course (Noon et al, 2010), represents approximately 2% -3% in all malignant tumor, a median survival of approximately 1 yearb (Cohen et al, 2005;Sconocchia et al, 2009). Annual incidence increased at about 2%, nearly 100, 000 cases of patients died of kidney cancer each year.…”
Section: Discussionmentioning
confidence: 99%